CORRECTION DYSBACTERIOSIS IN REHABILITATION PROGRAMS FOR CHILDREN UNDERGOING SURGERY ON THE COLON AND ANORECTAL ZONE - V. A. Tarakanov; A. E. Strykovsky; M. A. Anokhina; V. M. Starchenko; V. M. Nadgeriev; A. N. Lunyaka; O. A. Tereshenko; A. V. Poleev (Кубанский научный медицинский вестник, 2017)
Rehabilitation of children undergoing surgery for colon and rectum is an important issue of pediatric surgery. Its relevance is due to the widespread development of these anomalies requiring surgical correction –  1:4000–5000 newborns. In all patients with this disease is marked by inflammatory changes in the intestinal mucosa. Use of      73  antibacterial drugs in the pre-and postoperative periods in 100% of cases, causes the development of  intestinal dysbiosis.Dysbiosis uniqueness is manifested in the fact that this disease is in the interests of doctors of different specialties. Traditional methods for correcting violations mikrobiotsinoz gut is not always sufficiently effective in surgical patients. The purpose of this study to optimize the treatment and prevention circuit dysbacteriosis in surgical patients.